Nantucket grand - Axelrod, Steven (Axelrod, Steven. Henry Kennis mystery., 2016)
During a long winter and short, chilly spring, a series of disturbing incidents rock the small resort island of Nantucket. A Land Bank executive dies in a suspicious hunting accident, a prominent local family's historic summer cottage burns down in an arson fire, and a teenage girl lies comatose from a drug overdose. When spring turns to summer and the tourists flood the island, the mysterious cycle of violence spins faster. A young Jamaican boy is found dead in the harbor, a sex-for-drugs pornography ring is exposed, and a beloved local hero is murdered in cold blood. Could all of these events be part of the same sinister conspiracy?